Black Women’s Labor and White Ally Development in an Urban Teacher Education Program - Coleman-King, Chonika; Anderson, Brittany N.; Koerber, Nathan (Frontiers in Education, 2021)
The article uses events and narratives from the perspectives of Black women professors as examples of how allyship can be birthed and to illustrate the roles, responsibilities, and risks inherent in allyship development and work. It focuses on the labor needed to establish and sustain allyships as critical anti-racist educators in an Urban Teacher Preparation Program at a Historical White Institution. Dispositions of White allies are discussed, in addition to the various tentions allies may face in creating and sustaining equitable spaces and practices. Considerations for reciprocity are also offered to better support faculty of color.